تطوير مادة تعليم مهارة القراءة بالمدخل منهج 2013 على أساس برنامج لقتورا انفيير في مدرسة محمدية سوجه واراس الثانوية بوجونجارا - Muhammad Rondi Rondi (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2023)
The result of requirement analysis showed that the teaching materials included on learning media has not been appropriate yet with the 2013 curriculum. One of the factors behind is the learning process in the classroom still uses lecture method and reading method. The purpose of this research is to know how to develop teaching materials by using Lectora Inspire software that can be used in learning qiraah, know its specification and apply the software in learning qiraah to increase students’ interest and learning outcomes. Research method used in this research is Research and Development (R & D) with research design of pre-test and post-Test control group design. The steps in this study include the analysis of problems and needs, data collection, product design, design validation to media experts and material experts, design revisions, product testing to students of class X SMA Muhammadiyah Sugihwaras Bojonegoro with sample 25 students of experimental class. The teaching materials developed with lectora inspire software consist of six chapters which are all contained in the Arabic language of class X. Based on the results of media and material experts stated that those media developed belong proper category as learning media. The result of hypothesis test analysis by using T test showed that the value of significance = 0,000 <0,05 which means Ha accepted and Ho rejected. The mean score of the students of the experimental class is (83.2) greater than the average score of the control class students (69.4). The results of student questionnaires also indicated that the responses and students' assessment of the media is also positive. Therefore, it can be concluded that the development of reading skill with lectora inspire software for qiraah learning has a significant influence.